The Persistence of Poverty in Costa Rica: An Explanation Based on the Logit Model - Ortega Ortega, Ángel (2025)
This article seeks to analyze the causes of the lack of poverty reduction in Costa Rica. In recent decades, several governments have had the opportunity to develop their own strategies and have used the allocated resources to achieve this goal. The analysis is based on poverty statistics generated by the Institute of Statisticsand Census (INEC) for the years 2015–2019. This period represents the time reference for the analysis developed. The methodology consisted of constructing a logit statistical model designed to model variables and dimensions of influence on poverty in Costa Rica. The existing data allow us to define five dimensions considered by the INEC, as well as to determine criteria for explaining poverty, such as: employment status, health, education, housing, and social protection. The scenarios developed allow us to conclude that the weight of each dimension in explaining poverty is different, with the work dimension having the greatest weight. The lack of coverage in one or more of the twenty explanatory indicators of poverty that are part of the five variables leads to determining the relative deprivation of the human right not to be poor in Costa Rican society. Twenty indicators are also integrated into the respective analysis. The study allows for the construction of different scenarios that demonstrate the relative importance of each indicator in explaining poverty.